1988
DOI: 10.1007/bf01800369
|View full text |Cite
|
Sign up to set email alerts
|

Biotin‐responsive multiple carboxylase deficiency in an 8‐year‐old boy with normal serum biotinidase and fibroblast holocarboxylase‐synthetase activities

Abstract: An 8-year-old boy with late onset multiple carboxylase deficiency is described. Biotinidase deficiency and holocarboxylase-synthetase deficiency have been excluded. A very slow biochemical response to biotin was found. The decrease in urinary organic acid excretion followed first-order kinetics with a half-life of about 50 days. The initially low carboxylase activities in thrombocytes were increased but not normalized after 3 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In the present study, we identi®ed a mutation in the HCS gene of a patient who was originally reported as having late-onset MCD with normal serum biotinidase and ®broblast HCS activities [6]. The onset of symptoms in this patient occurred when he was 8 years old; the oldest reported onset of HCS de®ciency.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the present study, we identi®ed a mutation in the HCS gene of a patient who was originally reported as having late-onset MCD with normal serum biotinidase and ®broblast HCS activities [6]. The onset of symptoms in this patient occurred when he was 8 years old; the oldest reported onset of HCS de®ciency.…”
Section: Discussionmentioning
confidence: 88%
“…A patient who developed his ®rst episode of metabolic acidosis at 8 years and had the characteristic organic aciduria of MCD has been reported previously [6]. His clinical symptoms and organic aciduria were responsive to biotin therapy, although the decrease in his urinary 3-hydroxyisovalerate concentration was exceptionally slow.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The amelioration of her biochemical and clinical abnormalities after biotin treatment started was relatively slow among patients with HLCS [Holme et al, 1988]. This mutation resulted in abnormal splicing with a decreased level of normal mRNA .…”
Section: Clinical Relevance Founder Mutationsmentioning
confidence: 99%
“…As previously noted, some patients homozygous for this mutation may be asymptomatic. In spite of a rather mild phenotype associated with IVS1015G4A among HLCS-deficient patients at the onset, the clinical responses to biotin treatment are slow and partial in some cases [Holme et al, 1988;Santer et al, 2003]. …”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%